2015
DOI: 10.1002/elps.201400466
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical hematocrit determination in a direct current microfluidic device

Abstract: Hematocrit (HCT) tests are widely performed to screen blood donors and to diagnose medical conditions. Current HCT test methods include conventional microhematocrit, Coulter counter, CuSO4 specific gravity, and conductivity-based point-of-care (POC) HCT devices, which can be either expensive, environmentally inadvisable, or complicated. In the present work, we introduce a new and simple microfluidic system for a POC HCT determination. HCT was determined by measuring current responses of blood under 100 V DC fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…For this reason, biochemical analyses, such as biomarkers in cardiovascular diseases and disorders [ 4 ] or DNA [ 5 ], do not show sufficient promise for the early detection of cardiovascular diseases [ 6 ]. Since the associations between coronary heart diseases and blood rheology have been sufficiently investigated [ 3 , 7 , 8 ], several biophysical properties such as the viscosity [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], erythrocyte sedimentation rate (ESR) [ 17 , 18 , 19 , 20 , 21 , 22 ], hematocrit [ 23 , 24 , 25 ], aggregation [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ], and deformability [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] are employed to detect variations in blood samples. Among them, blood viscosity varies depending on several factors, such as the plasma viscosity, hematocrit, red blood cell (RBC) aggregation, and deformability.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, biochemical analyses, such as biomarkers in cardiovascular diseases and disorders [ 4 ] or DNA [ 5 ], do not show sufficient promise for the early detection of cardiovascular diseases [ 6 ]. Since the associations between coronary heart diseases and blood rheology have been sufficiently investigated [ 3 , 7 , 8 ], several biophysical properties such as the viscosity [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], erythrocyte sedimentation rate (ESR) [ 17 , 18 , 19 , 20 , 21 , 22 ], hematocrit [ 23 , 24 , 25 ], aggregation [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ], and deformability [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] are employed to detect variations in blood samples. Among them, blood viscosity varies depending on several factors, such as the plasma viscosity, hematocrit, red blood cell (RBC) aggregation, and deformability.…”
Section: Introductionmentioning
confidence: 99%
“…Then, by repeating the same PBS and 60% RBC solution measurement cycles, current responses could be restored to 60–63 μA again. These carbonized platinum electrodes demonstrated sufficient activity and stability to reproducibly measure RBC hematocrit to ∼2 vol% resolution .…”
Section: Resultsmentioning
confidence: 99%
“…Triton X‐100 attenuates electrolysis bubble effects that destabilize current responses by facilitating formation of smaller bubbles. It was shown that 320 μM Triton X‐100 does not compromise RBC membrane integrity .…”
Section: Methodsmentioning
confidence: 99%
“…Patients with serious CVDs have microcirculatory disorders that are found to be strongly associated with the biophysical properties of blood [2]. Hence, the biophysical properties of blood, such as the viscosity [3,4,5], hematocrit [6,7], RBC deformability [8,9], erythrocyte sedimentation rate (ESR) [10,11], RBC aggregation [12,13,14] and other factors [15,16,17], are widely tested to diagnose the pathological or physiological disorders of CVDs. Among the biophysical properties of blood, RBC aggregation is the major cause of the non-Newton flow properties of whole blood, and it has been popularly utilized to diagnose the inflammatory diseases in clinic, since the level of aggregation rises enormously in association with diabetes [18], sepsis [19], myocardial ischaemia [20] and so on.…”
Section: Introductionmentioning
confidence: 99%